Effect of a high-fat diet on male fertility and sperm physiology in high fertility performance mice - Cohen, Debora Juana (2019)
The prevalence of metabolic syndrome (MetS) has increased in alarming proportions, affecting around 20–25% of the global population.1 MetS has been defined as an increase in at least three of the following factors: abdominal obesity, blood pressure, triglycerides, cholesterol, and fasting glucose.2 Although MetS had been originally associated with advanced age, changes in lifestyle have accelerated the appearance of the symptoms, coinciding with reproductive age and becoming a risk factor for fertility disorders.